(untitled) ("Temas Sociais" Journal, 2023)
Social Work’s profession covers the most different problems in society. Social intervention considers that each phenomenon has its characteristics, in this sense, the professional must adapt to the space in which they are going to intervene. Home visits, in addition to benefiting from a long tradition in Social Work, are one of the privileged instruments for promoting more understanding and responsive responses to the supported people/families. This study was developed within the scope of the Curricular Unit Workshop of Practices in Social Work I, at Lusófona University – Porto University Center, and its main goal, through a literature review, was to address the home visit as a technical/operative instrument, highlighting the beginning of the home visit, the operationalization and the good practices adopted by social workers, particularly in matters of security, emotions, and confidentiality. We concluded that home visits help professionals increase the involvement of people/families, improve communication, and understand the social reality to carry out their intervention. Home visits have been a vital tool in articulating actions within the scope of Social Work throughout the history of the profession.